2021
DOI: 10.15225/pnn.2021.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19, Risk Perception and Stress Level in Polish Nurses During COVID-19 Outbreak

Abstract: Introduction. The outbreak of COVID-19 disease causes severe stress in health care workers, especially nurses. Nurses are at high risk of contracting the disease, as well as an increased risk of developing mental health symptoms such as fear, anxiety and work-related stress. Aim. The aim of the study was to determine the relationship between fear of COVID-19, risk perception, perceived threat and stress in Polish nurses during COVID-19 outbreak. Material and Methods. 106 nurses participated in the study. Perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In addition, there may be fewer healthcare workers on maternity wards than there were before the pandemic due to the relocation of staff to infectious departments and infections or quarantine of the staff. Healthcare workers may also limit contact with women because of fear of infection [ 19 , 44 , 50 , 51 , 52 ]. Therefore, many studies indicate increased fear of childbirth caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be fewer healthcare workers on maternity wards than there were before the pandemic due to the relocation of staff to infectious departments and infections or quarantine of the staff. Healthcare workers may also limit contact with women because of fear of infection [ 19 , 44 , 50 , 51 , 52 ]. Therefore, many studies indicate increased fear of childbirth caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted among Polish nurses during the COVID-19 pandemic confirms that the vast majority of them experienced increased symptoms of stress [ 10 , 34 ], largely due to changes in the existing workplace organisation and the fear of transmitting the disease to their family. However, after a year of working during the pandemic, stress remained at medium and low levels, which may indicate a phase of adaptation to the public health crisis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distress, on the other hand, has a negative or even destructive effect and is difficult to control [ 8 ]. Research conducted during the COVID-19 pandemic confirms that Polish nurses experienced severe stress and perceived the pandemic as an important threat to their health and safety [ 9 , 10 ]. This means that during the COVID-19 pandemic, nurses, along with other healthcare workers, experienced distress, which was mainly related to the experience of fear, risk related to treating an infected patient, numerous deaths of patients and staff, uncontrolled emergency situations, and long work shifts [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the extraordinary time of the pandemic, which affected the whole world, nurses stood on the front lines of the fight against the disease. This phenomenon has had many psychological consequences for healthcare workers [ 17 ]. Our results show that nurses who participated in hybrid education and who had no fear of their own deaths due to SARS-CoV-2 were not afraid of coming in contact with other healthcare workers either at work or outside the workplace and did not experience an increased feeling of stress while performing nursing duties for patients during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific studies by other authors indicate that, during the pandemic, nurses experienced a fear of infection, death, and the loss of a loved one, as well as of contact with people who might be infected [ 18 ]. Moreover, the perception of infection risk among Polish nurses was a predictor of perceived stress [ 17 ]. It can be concluded that nurses who accepted the occupational risk of the accompanying pandemic and the consequences of this phenomenon were more positive about caring for a dying patient.…”
Section: Discussionmentioning
confidence: 99%